Assessment of breeding practice and evaluation of estrus synchronization of dairy cattle in Sidama Zone, southern Ethiopia - Legesse, D. (Hawassa University, 2016)
Breeding practices, evaluation of estrus synchronization and milk progesterone profile study was conducted in Sidama zone. The study was conducted at two agro ecological zones (highland and midland) of the zone to assess the prevailing cattle breeding practices. Data was collected using semi structured questionnaire and focus group discussion. A total of 180 respondents were randomly selected from the 9 kebeles and included in the study. The survey results indicated that the average age at first service for native and crossbred heifers were (42.2±4.4 and 30.3±4.4) months. The average age at first calving for native and crossbred was (51.9±5.9and 39.3±3.9 months). Panmectic mating system was common in the study area. Most of the respondents do not own their own bulls but rely on the bulls owned by their acquaintances. The study further indicated that the respondents selected animals based on their higher milk yield, followed by breeding ability, growth rate and low intake of feed. There was lack of awareness among the respondents in estrus detection and time of insemination. Thus in most of the cases the AM/PM rule for insemination is not followed. Majority of the respondents were not satisfied with the results of the estrus synchronization and mass insemination (OSMI) program as the conception rate in the cattle was much below their expectation. The results pertaining to the evaluation of the synchronized cattle under the mass insemination program indicated that the estrus response interval differed (P<0.05) among the native and the crossbred cattle while the values were (68.6±1.9) hours among the native and (56.0±2.0) hours among the crossbred cattle. The average number of services per conception was higher among the native cattle (2.4) when compared to that of the crossbreds (1.83). However, the conception rate was higher among the crossbreds vis-a vis that of the native cattle. The results further indicate that the conception varied across the agro ecologies with the values being higher in the 1st parity among the cattle reared in the midlands while the same was higher in the 2nd parity among the cattle reared in the highlands. The body condition score was higher (P<0.05) among the cattle with exhibited better conception rate. Conception rate varied across the agro ecologies with higher rate of conception observed among the cattle reared in the highlands. Conception also varied across the age of the cow with higher values observed among those aged between 5-7 years or in the second parity. The optimum conception was observed among the cows inseminated between 10-15 hours after the onset of estrus. The rate of conception too varied (P<0.05) across the bulls whose semen was used to artificially inseminated cows. The rate of estrus response was higher in the action research when compared to those involved in the mass insemination. Pregnancy diagnosis following milk progesterone profile using Hormonst micro-lab farmer test kit indicated that most of the early embryonic mortalities were observed within 28 to 46th days post insemination. The effect of genetic and non-genetic factors contributed to the success of conception in cattle. Use of Hormonst micro-lab farmertest can be an effective tool to identify the pregnancy status of the cattle much ahead of the traditional rectal palpation method.